Linguistic categories, language description and linguistic typology - Alfieri, Luca; Arcodia, Giorgio Francesco, 1978-; Ramat, Paolo (Typological studies in language ;, 2021)
"Few issues in the history of the language sciences have been an object of as much discussion and controversy as linguistic categories. The eleven articles included in this volume tackle the issue of categories from a wide range of perspectives and with different foci, in the context of the current debate on the nature and methodology of the research on comparative concepts - particularly, the relation between the categories needed to describe languages and those needed to compare languages. While the first six papers deal with general theoretical questions, the following five confront specific issues in the domain of language analysis arising from the application of categories. The volume will appeal to a very broad readership: advanced students and scholars in any field of linguistics, but also specialists in the philosophy of language, and scholars interested in the cognitive aspects of language from different subfields (neurolinguistics, cognitive sciences, psycholinguistics, anthropology)"--